2020
DOI: 10.5194/bg-17-361-2020
|View full text |Cite
|
Sign up to set email alerts
|

Lability classification of soil organic matter in the northern permafrost region

Abstract: Abstract. The large stocks of soil organic carbon (SOC) in soils and deposits of the northern permafrost region are sensitive to global warming and permafrost thawing. The potential release of this carbon (C) as greenhouse gases to the atmosphere does not only depend on the total quantity of soil organic matter (SOM) affected by warming and thawing, but it also depends on its lability (i.e., the rate at which it will decay). In this study we develop a simple and robust classification scheme of SOM lability for… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 53 publications
1
21
0
Order By: Relevance
“…The study of talik sediments is however highly relevant for climate studies as it allows important insights into the pathways of previously frozen OM upon rapid thaw and thus the potential for GHG production below thermokarst lakes. While many studies suggested a higher biolability of old Yedoma OM upon thaw compared to Holocene thermokarst deposits (Dutta et al, 2006;Jongejans et al, 2018;Lee et al, 2012;Neubauer, 2016;Schuur et al, 2009;Strauss et al, 2015Strauss et al, , 2017Zimov et al, 2006), a few studies showed opposite findings (Kuhry et al, 2020;Schädel et al, 2014). Furthermore, climatic conditions during permafrost formation were shown to play a crucial role for OM decomposition after thaw (Knoblauch et al, 2013;Walz et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The study of talik sediments is however highly relevant for climate studies as it allows important insights into the pathways of previously frozen OM upon rapid thaw and thus the potential for GHG production below thermokarst lakes. While many studies suggested a higher biolability of old Yedoma OM upon thaw compared to Holocene thermokarst deposits (Dutta et al, 2006;Jongejans et al, 2018;Lee et al, 2012;Neubauer, 2016;Schuur et al, 2009;Strauss et al, 2015Strauss et al, , 2017Zimov et al, 2006), a few studies showed opposite findings (Kuhry et al, 2020;Schädel et al, 2014). Furthermore, climatic conditions during permafrost formation were shown to play a crucial role for OM decomposition after thaw (Knoblauch et al, 2013;Walz et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…1b). The land surface within the alas basins is covered by grasslands, whereas the boreal forest found on the Yedoma uplands mainly consists of Larix cajanderi with several Pinus sylvestris communities (Kuznetsova et al, 2010;Ulrich et al, 2017b). Central Yakutian alas landscapes are characterized by extensive land use, which mainly consists of horse and cattle herding and hay farming (Crate et al, 2017).…”
mentioning
confidence: 99%
“…9) drives the differentiation into large plant-derived, less decomposed POM and mostly microbial-dominated small POM in the studied permafrost-affected soils. The less decomposed fibrous fPOM and oPOM are hotspots for microbial activity and, thus, for the decay of these larger plant structures (Kuzyakov and Blagodatskaya, 2015). These hotspots for the formation of MAOM in Cryosols, plant residues in direct contact with silt-to clay-sized mineral particle surfaces, were already demonstrated on intact Cryosol cross sections using spectromicroscopic imaging (Mueller et al, 2017).…”
Section: Som Fractionmentioning
confidence: 88%